Examining the substance use, violence, and HIV and AIDS (SAVA) syndemic among urban refugee youth in Kampala, Uganda: cross-sectional survey findings. (7th July 2022) - Logie, Carmen H.; Okumu, Moses; Malama, Kalonde; Mwima, Simon; Hakiza, Robert; Kiera, Uwase Mimy; Kyambadde, Peter
Abstract : Background: Interactions between substance use, violence, HIV and AIDS, known as the 'SAVA' syndemic, are understudied among refugee youth. We assessed the synergistic effects of frequent alcohol use, depression and violence on HIV vulnerability among urban refugee youth aged 16–24 years in Kampala, Uganda. Methods: We conducted a cross-sectional survey between January and April 2018 with a convenience sample of refugee youth aged 16–24 years living in informal settlements in Kampala (Kabalagala, Rubaga, Kansanga, Katwe, Nsambya). We assessed non-communicable health conditions (frequent [≥3 times per week] alcohol use [FAU]; depression); violence (young adulthood violence [YAV] at age ≥16 years, intimate partner violence [IPV]), and HIV vulnerability (past 12-month transactional sex; recent [past 3-month] multiple [≥2] sex partners). We calculated the prevalence and co-occurrence of non-communicable health conditions, violence and HIV vulnerability variables. We then conducted multivariable logistic regression analyses to first create unique profiles of FAU, depression, YAV and IPV exposures, and second to assess for interactions between exposures on HIV vulnerability outcomes. Results: Most participants (n=445; mean age: 19.59, SD: 2.6; women: n=333, 74.8%, men: n=112, 25.2%) reported at least one non-communicable health condition or violence exposure (n=364, 81.8%), and over half (n=278, 62.4%) reported co-occurring exposures. One-fifth reported FAU (n=90; 20.2%) and one-tenth (n=49; 11%) major depression. In logistic regression models including all two-way product terms, adjusted for sociodemographics, we found (a) multiplicative interaction for joint effects of FAU and IPV (adjusted OR (aOR)=4.81, 95% CI: 1.32 to 17.52) on multiple sex partners, and (b) multiplicative interaction for joint effects of FAU and IPV (aOR=3.72, 95% CI: 1.42 to 9.74), and YAV and depression (aOR=7.13, 95% CI: 1.34 to 37.50), on transactional sex. Conclusion: Findings signal the importance of addressing the SAVA syndemic among urban refugee youth in Uganda. Synergistic interactions indicate that addressing FAU, depression or violence may concomitantly reduce HIV vulnerability with urban refugee youth.